A Financial Performance of Indian Banks Using CAMELS Rating System - Banu, Meraj; Vepa, Sudha (The journal of contemporary issues in business and government, 2021)
Undoubtedly, the banking system in India has witnessed the fastest growth in comparison to other governing sectors of the Indian economy. The solvency and sustenance of banks do not only concern the depositors but equally to the other participants viz., the employees, the customers, the shareholders and the country as a whole. The banking system’s assistance in smooth functioning of trade and commerce across the globe indicates an imperative need for its timely and regular monitoring. The study aims at analysing the financial and operating performance of the Indian Banking Sector. The HDFC and ICICI as the largest private banks and State Bank of India (SBI) and Syndicate Bank as the largest public sector banks are selected for this purpose. The evaluation is done using CAMELS rating system as recommended by Padmanabhan Committee. The various ratios, noted below, are considered for the study based on CAMELS acronym in the following order. Capital Adequacy ratios Asset Quality ratios Management Capability ratios Earnings Quality ratios Liquidity ratios and Sensitivity to market risk The period, considered, is from 2010 – 2019. The descriptive statistics is used to analyse the results thereof. Correlation and t -test are executed to test the hypothesis.